DIGITAL INTERPRETATION IN THE SOCIAL MEDIA ERA: THETRANSFORMATION OF RELIGIOUS AUTHORITY AND THE CRISIS OF RELIGIOUS MODERATION - Cahyono, Agung Mandiro; Mukti, Anwar; Hakim, M. Luqman; Bahrudin, Moh.; Fathoni, Ahmad Nur; Azzahro, Ana Asyifa (Westscience Press, 2025)
The development of digital technology and social media has fundamentally changed the way religious information is disseminated, shifting society's dependence from traditional religious institutions to the consumption of abundant digital religious content on the internet. This transformation has not only reshaped religious authority, but also increased the potential for a decline in religious moderation due to the spread of inaccurate, biased, and radical interpretations. This study aims to analyze the shift in religious authority in the context of Islamic interpretation in the digital age and explore the role of social media in spreading radical ideology. Through a qualitative approach using a systematic literature review of scientific publications from 2019 to 2025, thematic analysis shows a shift from hierarchical authority based on religious scholars and religious institutions to authority based on popularity on social media, which contributes to vulnerability to misinformation, fragmentation of religious understanding, and commodification of religion. Digital literacy emerges as a key factor in filtering religious information, but access to it is not yet evenly distributed among the public. This study concludes that the transformation of religious authority in the digital era is an inevitability that has dual impacts: it opens up opportunities for the democratization of knowledge but also has the potential to erode religious moderation. Therefore, collaboration between the government, religious institutions, and the community is needed to strengthen religious digital literacy and develop responsive content regulations.